Komunikasi Matematis Siswa melalui Pembelajaran Berbantuan Modul Digital Daring - Pramuditya, Surya Amami; Khodijah, Atina Sabila; Asnawati, Sri (Edumatica : Jurnal Pendidikan Matematika, 2021)
Mathematical communication is one of the mathematical abilities that need to be mastered by students because mathematical communication has an important role in linking ideas and abstract language with mathematical symbols. Meanwhile, digital modules based on several previous studies are considered practical and can improve mathematics learning outcomes. Therefore, the online digital module was used as a supporting medium in this research. This study aims to describe the profile of students' mathematical communication skills through online digital module-assisted learning. The approach used is a qualitative approach with a descriptive method. The subjects in this study were grade IX students from one of the public junior high schools in Majalengka Regency as many as three people with better cognitive abilities than other students. The instruments used are tests and interview guidelines. The results of the study: (1) S-1 has high mathematical communication skills capable of fulfilling 5 of 6 sub-indicators; (2) S-2 has moderate mathematical communication skills and can fulfill 3 of the 6 sub-indicators; (3) S-3 has low mathematical communication skills and can fulfill 3 of the 6 sub-indicators with more errors in completion. The conclusion is that students can communicate their ideas based on things they have understood from the module such as ideas for solving SPLTV problems and the steps for solving them.